ЕНЕРГЕТИЧНІ ПОКАЗНИКИ ТЕРМІЧНИХ ОПРІСНЮВАЛЬНИХ СИСТЕМ ЗІ ЗВОЛОЖУВАЧАМИ РІЗНИХ ТИПІВ - Середа, В. В.; Притула, Н. О. (Вісник Вінницького політехнічного інституту, 2023)
The demand for potable water is increasing worldwide due to population growth, urbanization, industrialization, agricultural activity, and socio-economic development. One of the solutions of this problem is the development of reliable and cost-effective autonomous decentralized water desalination systems. The air humidification-dehumidification cycle is a promising method of thermal water desalination. Such systems have a simple design, low initial and operating costs and use renewable energy to operate. The directions of development of thermal water desalination technology with air humidification-dehumidification cycle are considered. The main indicators used to evaluate the efficiency of such systems are noted. It is shown that the main element that determines the performance of the installation is a humidifier — a contact heat exchanger for evaporating moisture from salt water into the air. A review of scientific works on experimental studies of the most common types of humidifiers was carried out. The advantages and disadvantages of the proposed constructions were determined and their energy indicators were analyzed (energy efficiency coefficient, fresh water consumption, mass flow coefficient, recovery coefficient and aerodynamic pressure drop). Graphical dependencies of thermodynamic efficiency on the mass flow rate and aerodynamic pressure drop on the specific productivity for different types of humidifiers are plotted. It was found that in order to provide high thermodynamic efficiency, humidifiers with packing material and bubble heat exchangers require high mass flow rate of salt water and have significant aerodynamic pressure drop. The absence of measurements of water and air pressure drops was established in most experimental studies. Further directions for improving the efficiency of thermal desalination plants with air humidification-dehumidification cycle are outlined.